ANALISIS SEMIOTIKA PIERCE PADA FILM ANIMASI PORORO TERHADAP PENANAMAN NILAI KARAKTER PADA ANAK - Nurinsani, Wafi Fathi; Heryati, Yeti; Laeli, Wardah (Jurnal Metrum, 2025)
This article analyzes the animated film Pororo the Little Penguin using Charles Sanders Peirce’s semiotic approach, with a focus on character education values that can be transmitted to children. This study employs a qualitative method with a phenomenological approach to describe and analyze phenomena that emerge from the collected data. The data were obtained through film observation and interviews with informants, including Mrs. Lelis, who served as the primary source in understanding the film’s influence on character development in children. The findings reveal that visual elements in the film—such as icons, indexes, and symbols—play a significant role in helping children understand and internalize moral values such as honesty, cooperation, and friendship. Through the analysis of selected episodes, it is evident that the film functions not only as a source of entertainment but also as an effective tool for conveying messages of character education.